(Research into Expectations of College Mathematics Instructors) - Nowlan, Robert A. (1994)
Keywords: dept.mat; faculty_collection; sabbatical_report

Discrete Mathematics. - Gulati, Bodh R. (1992)
Keywords: dept.mat; faculty_collection; sabbatical_report

Integration of the Use of Computer Technology in Teaching Mathematics. - Bass, Helen (1991)
Keywords: dept.mat; faculty_collection; sabbatical_report

Study of Symbolic Computation Systems (Computer Algebra Systems) - Meck, Michael (1990)
Keywords: dept.mat; faculty_collection; sabbatical_report

Born This Day: A Book of Birthdays and Quotations of Prominent People Through the Centuries - Nowlan, Robert A. (McFarland, 1996)
Keywords: Quotations; English; Birthday books; Literary calendars; dept.mat; faculty_collection

We'll Always Have Paris: The Definitive Guide to Great Lines from the Movies - Nowlan, Robert A.; Nowlan, Gwendolyn Wright (HarperCollins Publishers, 1995)
Keywords: Motion pictures; Quotations; maxims; etc; dept.ils; dept.mat; faculty_collection

Finite Mathematics with Applications to the Business and Social Sciences - Gulati, Bodh R. (Kendall/Hunt Pub. Co., 1994)
Keywords: Mathematics; dept.mat; faculty_collection

Film Quotations: 11,000 Lines Spoken on Screen, Arranged by Subject, and Indexed - Nowlan, Robert A. (McFarland, 1994)
Keywords: Motion pictures; Quotations; maxims; etc; dept.mat; faculty_collection

The Films of the Eighties: A Complete, Qualitative Filmography to Over 3400 Feature-Length English Language Films, Theatrical and Video-Only, Released Between January 1, 1980, and December 31, 1989 - Nowlan, Robert A.; Nowlan, Gwendolyn Wright (McFarland & Co., 1991)
Keywords: Catalogs; Motion pictures; dept.ils; dept.mat; faculty_collection

Movie Characters of Leading Performers of the Sound Era - Nowlan, Robert A. (American Library Association, 1990)
Keywords: Biography; Characters and characteristics in motion pictures; Dictionaries; Dictionaries; Film adaptations; Dictionaries; Motion picture actors and actresses; dept.mat; faculty_collection

Cinema Sequels and Remakes, 1903-1987 - Nowlan, Robert A. (McFarland & Co., 1989)
Keywords: Film remakes.; Film sequels.; dept.mat; faculty_collection

College Algebra and Trigonometry with Applications - Gulati, Bodh R. (Allyn and Bacon, 1986)
Keywords: Algebra; Trigonometry; dept.mat; faculty_collection

College Algebra with Applications - Gulati, Bodh R. (Allyn and Bacon, 1986)
Keywords: Algebra; dept.mat; faculty_collection

The College of Trivial Knowledge - Nowlan, Robert A. (Quill, 1983)
Keywords: FAQs.; dept.mat; faculty_collection

Algebra and Trigonometry: Precalculus Mathematics - Gulati, Bodh R. (Allyn and Bacon, 1982)
Keywords: Algebra; Trigonometry; dept.mat; faculty_collection

College Algebra - Gulati, Bodh R. (Allyn and Bacon, 1982)
Keywords: Algebra; dept.mat; faculty_collection

A Mathematical Panorama: Topics for the Liberal Arts - Berlinghoff, William P.; Gulati, Bodh R.; Grant, Kerry E. (D.C. Heath, 1980)
Keywords: Mathematics; dept.mat; faculty_collection

College Mathematics with Applications to the Business and Social Sciences - Gulati, Bodh R. (Harper & Row, 1978)
Keywords: Mathematics; Business mathematics; Social sciences; Methodology; dept.mat; faculty_collection

Finite Mathematics: An Introduction - Gulati, Bodh R. (Harper & Row, 1975)
Keywords: Mathematics; dept.mat; faculty_collection

Geometry for Teachers - Nowlan, Robert A.; Washburn, Robert M. (1973)
Keywords: Geometry; dept.mat; faculty_collection

Mathematics; the Art of Reason - Berlinghoff, William P. (Heath, 1968)
Keywords: Mathematics; dept.mat; faculty_collection

An isoperimetric inequality involving conformal mapping - Berlinghoff, W.P.; Reid, J.D. (Proceedings of the American Mathematical Society, 1977)
This paper characterizes quasi-pure projective (q.p.p.) and quasi-pure injective (q.p.i.) p-groups, and hence characterizes all such (abelian) torsion groups. A p-group is q.p.i. if and only if it is the direct sum of a divisible group and a torsion complete group. A nonreduced p-group is q.p.p. if and only if it is the direct sum of a divisible group and a bounded group; a reduced p-group is q.p.p. if and only if it is a direct sum of cyclic groups. © 1977 American Mathematical Society.
1 citations (Crossref) [2023-10-31]
Keywords: Abelian group; Direct sum of cyclic groups; Pure exact sequence; Quasi-injective; Quasi-projective; Torsion complete; dept.mat

On two level symmetrical factorial designs - Kounias, E.G.; Gulati, B.R. (Annals of the Institute of Statistical Mathematics, 1972)
0 citations (Crossref) [2023-10-31]
Keywords: dept.mat

Correction note to "on maximal (k,t)-sets" - Gulati, B.R. (Annals of the Institute of Statistical Mathematics, 1971)
1 citations (Crossref) [2023-10-31]
Keywords: dept.mat

A study of H-spaces via left translations - Nowlan, R.A. (Pacific Journal of Mathematics, 1971)
H-spaces are examined by studying left translations, actions and a homotopy version of left translations to be called homolations. If (F, m) is an H-space, the map s: F-→FF given by s(x) = Lx, i.e. s(x) is left translation by x, is a homomorphism if and only if m is associative. In general, s is an An-map if and only if (F, m) is an An+1 space. The action r: FF × F → F is given by r(φ, x) = φ(x). The map s respects the action only of left translations. In general, s respects the action of homolations up to higherorder homotopies. Each homolation generates a family of maps to be called a homolation family. Denoting the set of all homolation families by H∞(F), s: F -→ FF factors through F → H∞(F) and this latter map is a homotopy equivalence. © 1971 Pacific Journal of Mathematics.
0 citations (Crossref) [2023-10-31]
Keywords: dept.mat

Nonnegativity results for generalized q-binomial coefficients - Fishel, S. (Discrete Mathematics, 1995)
Let q be a prime number. The number of subgroups of order qk in an abelian group G of order qn and type λ is a polynomial in q, [kλ′]q. In 1987, Lynne Butler showed that the first difference, [kλ′] - [k - 1λ′], has nonnegative coefficients as a polynomial in q, when 2k ≤ |λ|. We generalize the first difference to the rth difference, and give conditions for the nonnegativity of its coefficients. © 1995.
1 citations (Crossref) [2023-10-31]
Keywords: dept.mat

Quadruple covers of algebraic varieties - Hahn, D.W.; Miranda, R. (Journal of Algebraic Geometry, 1999)
Let X and Y be varieties over a field k; π : X → Y is a quadruple cover of Y if π*script O signX is a locally free, rank 4 script O signY-algebra. If char k ≠ 2, we see that π*script O signX splits as script O signY ⊕ε where ε is a locally free rank 3 sheaf over script O signY, which is locally the "trace zero" module. For each y ∈ Y, we therefore have a rank 4 associative, commutative algebra over script O signY,y. We find that these algebras are parametrized by an affine cone over the Grassmanian G(2, 6) with vertex corresponding to the algebra k[x, y, z]/(x, y, z)2. We then show that a quadruple cover with trace zero module ε over a variety Y is determined by a totally decomposable section η ∈ H0(∧2S2 E* ⊗ ∧3 E). We then examine the case in which the section η has no zeros. Here, each rank 4 algebra may be associated to a pencil of conics. As a special case of this, we look at the work of G. Casnati and T. Ekedahl on Gorenstein covers, and we show that their analysis is the subcase where the pencil of conics has length 4 base locus. Finally, we study the case in which the trace zero module ε is split. In this context, Galois covers, which are covers induced by the action of a group of order 4 on the covering variety X, are also studied.
Keywords: dept.mat; ⛔ No DOI found

On maximal t-linearly independent sets - Gulati, Bodh Raj; Johnson, Bruce McK.; Koehn, Uwe (Journal of Combinatorial Theory, Series A, 1973)
Consider a finite t + r − 1 dimensional projective space PG(t + r − 1, s) over a Galois field GF(s) of order s = ϱh, where ϱ and h are positive integers and ϱ is the prime characteristic of the field. A collection of k points in PG (t + r − 1, s) constitutes an L(t, k)-set if no t of them are linearly dependent. An L(t, k)-set is maximal if there exists no other L(t, k′)-set with k′ > k. The largest k for which an L(t, k)-set exists is denoted by Mt(t + r, s). K. A. Bush [3] established that Mt(t, s) = t + 1 for t ⩾ s. The purpose of this paper is to generalize this result and study Mt(t + r, s) for t, r, and s in certain relationships.
8 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/049-844-927-071-25X, pop00074 tex.type: [object Object]
Keywords: dept.mat; information; theoretical study

An apparently algebraic property of the integers - Berlinghoff, W P (Mathematics Magazine, 1973)
0 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/026-438-128-219-467 tex.type: [object Object]
Keywords: dept.mat

Maximal sets of points in finite projective space, no t-linearly dependent - Gulati, Bodh Raj; Kounias, E G (Journal of Combinatorial Theory, Series A, 1973)
Consider a finite (t + r - 1)-dimensional projective space PG(t + r - 1, s) based on the Galois field GF(s), where s is prime or power of a prime. A set of k distinct points in PG(t + r - 1, s), no t-linearly dependent, is called a (k, t)-set and such a set is said to be maximal if it is not contained in any other (k*, t)-set with k* > k. The number of points in a maximal (k, t)-set with the largest k is denoted by mt(t + r, s). Our purpose in the paper is to investigate the conditions under which two or more points can be adjoined to the basic set of Ei, i = 1, 2, ..., t + r, where Ei is a point with one in i-th position and zeros elsewhere. The problem has several applications in the theory of fractionally replicated designs and information theory. © 1973.
7 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/034-767-610-500-30X tex.type: [object Object]
Keywords: dept.mat; melampolide

3 Level Symmetrical Factorial Designs and Ternary Group Codes - Gulati, BR; Kounias, EG (Sankhya-the Indian Journal of Statistics Series A, 1973)
tex.unique-id: ISI:A1973T871800011
Keywords: dept.mat; ⛔ No DOI found

More about maximal (n, r)-sets - Gulati, Bodh Raj (Information & Computation, 1972)
Consider a finite r-dimensional projective space PG(r, s) based on the Galois field GF(s) where s is prime or power of a prime. A set of n distinct points in PG(r, s), no t linearly dependent, is said to be maximal or complete if it is not contained in any other set with n* points with n* > n. The number of points in a maximal set is denoted by mt(r + 1, s). The purpose of this paper is to improve the existing bounds for m5(r + 1, s) for r ≥ 5 and s ≥ 5 (odd). The investigation of maximal sets in certain relationships of t, r and s yields parity check matrices of (r + 1) rows and n columns with elements from GF(s) satisfying the condition that no t columns are linearly dependent. This problem has applications to coding theory and also in the theory of fractionally replicated designs. © 1972 Academic Press, Inc.
2 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/060-968-103-549-655 tex.type: [object Object]
Keywords: dept.mat

On maximal (k,t)-sets - Gulati, Bodh Raj (Annals of the Institute of Statistical Mathematics, 1971)
This investigation was originally motivated by the problem of determining the maximum number of points in finite n-dimensional projective space PG(n, s) based on the Galois field GF(s) of order s=ph (where p and h are positive integers and p is the prime characteristic of the field), such that no t of these chosen points are linearly dependent. A set of k distinct points in PG(n, s), no t linearly dependent, is called a (k, t)-set for k1 >k. The maximum value of k is denoted by mt (n+1, s). The purpose of this paper is to find new upper bounds for some values of n, s and t. These bounds are of importance in the experimental design and information theory problems. © 1971 Institute of Statistical Mathematics.
3 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/034-537-832-802-203 tex.type: [object Object]
Keywords: dept.mat

Orthogonal arrays of strength five - Gulati, Bodh Raj (Trabajos De Estadistica Y De Investigacion Operativa, 1971)
1 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/036-805-328-988-003 tex.type: [object Object]
Keywords: dept.mat

Note on the cochran Q test - Tate, Merle W; Brown, Sara M (Journal of the American Statistical Association, 1970)
Cochran’s Q test for differences between related-sample percentages or proportions has generally been incorrectly presented in secondary sources. The most common mistake results from failure to recognize that rows containing only 1’s or only 0’s, i.e., only successes or only failures, do not affect the value of Q. The F test, however, is affected by such rows. The probabilities from the χ2 and F approximations are compared with the exact probabilities in three sets of data. A rule of thumb, based on extensive study of the distribution of 0 in small samples, is given as an aid in judging when the χ2 approximation is satisfactory for practical purposes. © Taylor & Francis Group, LLC.
24 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/029-237-766-585-590 tex.type: [object Object]
Keywords: dept.mat

Statistics for special q, t-kostka polynomials - Fishel, Susanna (Proceedings of the American Mathematical Society, 1995)
Kirillov and Reshetikhin introduced rigged configurations as a new way to calculate the entries of the Kostka matrix. Macdonald defined the two-parameter Kostka matrix whose entries generalize. We use rigged configurations and a formula of Stembridge to provide a combinatorial interpretation of in the case where is a partition with no more than two columns. In particular, we show that in this case, has nonnegative coefficients. © 1995 American Mathematical Society.
1 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/082-420-581-698-924
Keywords: dept.mat

Canonical bases for the Brauer centralizer algebra - Fishel, Susanna; Grojnowski, I (Mathematical Research Letters, 1995)
Citation Key Alias: lens.org/069-225-958-557-87X tex.type: [object Object]
Keywords: dept.mat

Applications über alles: mathematics for the liberal arts - Aboufadel, Edward F (Primus, 1994)
This paper presents a fresh approach to a general education mathematics course. The basic idea is to turn the customary mathematics class on its head by focusing on applications first, through a reading of articles from magazines and newspapers, and then turning to the technical mathematical details. A description of the topics that were covered in my course, along with references to various publications, is given. A course such as this one is important because it conveys how mathematics is serving the goals of society. © 1994 Taylor and Francis Group, LLC.
1 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/094-099-623-221-444 tex.type: [object Object]
Keywords: Applied mathematics; Coding theory; Discrete mathematics; General education courses; Geometry; Mathematics in government; Mathematics in industry; Probability; Statistics; dept.mat

Doing Statistics with OlympiaStat: Statistical Analysis Package Version 1.0: Explorations in Data Analysis Using a Spreadsheet Based Statistical Tool - Pelosi, Marilyn K.; Sandifer, Theresa M. (John Wiley & Sons, Inc., 1994)
Citation Key Alias: lens.org/038-766-935-839-978, pop00186
Keywords: dept.mat

Color spreading algorithm for the retail industry - Pelosi, Marilyn K; Sandifer, Theresa M; Sandifer, C Edward (Annual Conference on Computers, 1992)
One of the problems which many companies face is the distribution of inventory from one or more centrally located distribution centers. The retail, industry, and in particular the women's clothing industry, faces the additional problem that not only does the merchandise have to be distributed but it must be distributed in such a way that every store gets a reasonable spread of colors and sizes. This research attempts to optimize the multi-criteria allocation objective by developing a computer algorithm. In order to be implemented any algorithm developed must be computationally efficient due to the size of the industry and other system related programming constraints. The algorithm which was developed not only provided a solution which was a marked improvement regarding the color spread of the merchandise but was also efficient enough to be immediately implemented on a national basis. © 1992.
0 citations (Crossref) [2023-10-31] tex.type: Proceedings paper
Keywords: Algorithms; Garment manufacture; Multi-criteria allocation objective; Retail industry color spreading algorithm; Retail stores; Women's clothing industry; dept.mat